2016
DOI: 10.1016/j.cemconres.2015.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Properties of magnesium silicate hydrates (M-S-H)

Abstract: Investigations of synthetic magnesium silicate hydrate (M-S-H) samples have shown that M-S-H aged for 1 year can exhibit variable compositions with molar Mg/Si ratios in the range 0.7 ≤ Mg/Si ≤ 1.5. At lower Mg/Si ratio, additional silica is present whereas brucite is observed for Mg/Si ≥1.3. FT-IR and 29 Si NMR data reveal a high degree of silicate polymerisation, indicating the formation of silicate sheets. TGA shows the presence of bound water and of hydroxyl groups bound to Mg and as silanol groups in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
228
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 271 publications
(279 citation statements)
references
References 49 publications
(60 reference statements)
32
228
0
Order By: Relevance
“…In both cases, no borates were detected in the solids by XRD, the peaks and signals in the XRD spectra were in agreement with those for M-S-H [19][20][21] and brucite (Figure 5a,d). Therefore, the higher boron sorption ratios in the solutions with silica were the result of formation of M-S-H.…”
Section: Influence Of Silica On Boron Sorption Reactionssupporting
confidence: 69%
See 1 more Smart Citation
“…In both cases, no borates were detected in the solids by XRD, the peaks and signals in the XRD spectra were in agreement with those for M-S-H [19][20][21] and brucite (Figure 5a,d). Therefore, the higher boron sorption ratios in the solutions with silica were the result of formation of M-S-H.…”
Section: Influence Of Silica On Boron Sorption Reactionssupporting
confidence: 69%
“…Recent investigations [22][23][24] have suggested that M-S-H, formed at the interface between cement with natural rock, can be expressed as (MgO) x -(SiO 2 ) y -(H 2 O) z with variable stoichiometric ratios of Mg:Si:H. The magnesium concentrations were controlled by the solubility of brucite [18] for the case of [B] ini = 0.46 mmol/L. In the case of [B] ini = 9.25 mmol/L, the liquid phase did not reach the equilibrium in 28 days therefore the magnesium concentrations were higher than reported value of M-S-H [20]. The IR spectra of the solid samples from the solutions with silica after 17 days (Figure 6b) are consistent with those of synthesized M-S-H phases [19][20][21][25][26][27] though there is a band at 665 cm −1 , corresponding to Si-O-Si bending vibrations [20,28], which was not observed in our samples.…”
Section: Influence Of Silica On Boron Sorption Reactionsmentioning
confidence: 99%
“…3 mm wide Mg-enriched zone along a 30 mm long interface sample was shown on SEM-EDAX composite element maps that coincided also with a Cadepleted zone. Small powder samples from this zone were examined by 29 Si-MAS-NMR and FTIR and the Mgbearing phase was identified as mainly Mg-Si-hydrate, also in analogy to spectra obtained from recent characterisation of synthetic Mg-Si-hydrates Roosz et al 2015;Nied et al 2016). Below, we complement this work and provide also details on the alteration observed on the claystone-side of the interface.…”
Section: Porosity Changes Across Interface Regionmentioning
confidence: 76%
“…This is also displayed in Fig. 4, where the M-S-H TG curve undergoes a progressive mass loss with lower slope from 235 o C until nearly 700 o C. This mass loss in M-S-H has been attributed to progressive dehydroxylation of disordered M-S-H, which has a range of hydroxyl environments [42]. This ongoing process is also noticeable in the temperature range above Mg(OH) 2 decomposition, where the DTG curve does not return to the values prior to the second peak.…”
Section: Xrd Characterizationmentioning
confidence: 79%